Respuesta :

Answer: C

Step-by-step explanation:

For this problem, you want to find (FoG)(x). Then, you want to find the inverse of that.

(FoG)=5(x-4)-6               [distribute]

(FoG)=5x-20-6               [combine like terms]

(FoG)=5x-26

Now, we want to find the inverse. To find the inverse, you switch the x with y and y with x, then solve for y.

y=5x-26                          [switch x with y and y with x]

x=5y-26                          [add both sides by 26]

x+26=5y                         [divide both sides by 5]

y=(x+26)/5

Now, we know that y=(x+26)/5 is the answer.

Wolfyy

Substitute [ x - 4 ] for x in the function of "R"

R(x) = 5(x - 4) - 6

R(x) = 5x - 20 - 6

R(x) = 5x - 26

Switch variables to find the inverse and solve for y

y = 5x - 26

x = 5y - 26

x + 26 = 5y

(x+26)/5 = y

Therefore, the answer is D.

Best of Luck!